2012
DOI: 10.1177/1745691612454303
|View full text |Cite
|
Sign up to set email alerts
|

Hindsight Bias

Abstract: Hindsight bias occurs when people feel that they "knew it all along," that is, when they believe that an event is more predictable after it becomes known than it was before it became known. Hindsight bias embodies any combination of three aspects: memory distortion, beliefs about events' objective likelihoods, or subjective beliefs about one's own prediction abilities. Hindsight bias stems from (a) cognitive inputs (people selectively recall information consistent with what they now know to be true and engage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
300
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(311 citation statements)
references
References 196 publications
7
300
0
4
Order By: Relevance
“…The distorted effort rating observed in the current study also bears resemblance to hindsight bias (22), reflecting a tendency to change recalled probability estimations once outcomes are known. As in a hindsight bias, retrospective change in effort estimation might reflect a general tendency to reshape memory contents to make them fit with an updated knowledge base (23).…”
Section: Fig 2 (A)supporting
confidence: 52%
“…The distorted effort rating observed in the current study also bears resemblance to hindsight bias (22), reflecting a tendency to change recalled probability estimations once outcomes are known. As in a hindsight bias, retrospective change in effort estimation might reflect a general tendency to reshape memory contents to make them fit with an updated knowledge base (23).…”
Section: Fig 2 (A)supporting
confidence: 52%
“…Whereas the memory design requires participants to make a naïve prediction and then recall this prediction after learning the actual outcome, the hypothetical design involves participants learning the actual outcome and then generating an estimate of what they would have predicted without the benefit of outcome knowledge. Although a sense-making process is presumed to underlie HB in the hypothetical design (Pezzo & Pezzo, 2007;Roese & Vohs, 2012), sense-making may also be initiated in the memory design conditional on a failed OJ recollection. If the OJ is not accessible, then individuals may attempt to make sense of the outcome by searching for viable explanations.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to HB more specifically, researchers have had some success in reducing HB when asking participants to list reasons for making their decision, to think of plausible alternative outcomes, and to provide evidence contrary to the outcome (Pezzo & Pezzo, 2007;Roese & Vohs, 2012;Slovic & Fischhoff, 1977). Furthermore, in the decision-making and cognitive aging literature, researchers have shown that strategies such as presenting less information (i.e., reducing cognitive load) when making complex decisions can effectively increase older adults' decision-making capabilities (e.g., medical decision, Wood et al, 2011).…”
Section: The Implications Of Hindsight Bias In Older Adultsmentioning
confidence: 99%
“…A problem relating to this type of study is hindsight bias-a belief that an event is more predictable after 3 Available at https://servicifi.wordpress.com/ICSME-2 it becomes known than it was before it became known [53]. In this research, it means that interviewees might tend to reconstruct the business goals based on the results of the impacts.…”
Section: Validitymentioning
confidence: 99%